2018
DOI: 10.1016/j.ultsonch.2018.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound- and microwave-assisted convective drying of carrots – Process kinetics and product’s quality analysis

Abstract: The aim of these studies was to investigate the influence of airborne ultrasound-assisted convective drying and microwave-assisted convective drying, as well as their combination, on process kinetics, total color change, water activity, content of carotenoids, polyphenols and antioxidant activity of carrots (Daucus carota L.). The global model of drying kinetics based on coupled ordinary differential equations was used to describe the moisture and material temperature profiles during drying. Application of ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 49 publications
9
44
0
3
Order By: Relevance
“…They reported that ΔE increased by increasing microwave power. Similar results had been reported by others for green pepper in US and microwave pretreatment under convective dryer (Szadzińska, Łechtańska, Kowalski, & Stasiak, 2017), carrot in hybrid US ‐ microwave ‐convective (Kroehnke et al, 2018) and soybeans in microwave dryer (Darvishi, 2017).…”
Section: Resultssupporting
confidence: 89%
“…They reported that ΔE increased by increasing microwave power. Similar results had been reported by others for green pepper in US and microwave pretreatment under convective dryer (Szadzińska, Łechtańska, Kowalski, & Stasiak, 2017), carrot in hybrid US ‐ microwave ‐convective (Kroehnke et al, 2018) and soybeans in microwave dryer (Darvishi, 2017).…”
Section: Resultssupporting
confidence: 89%
“…A wide diapason of studies of combined drying is considered. Combined drying processes are applied for different food products: fruits [1][2][3], vegetables [4][5][6][7][8], in chemical industry [9][10][11][12][13].…”
Section: Problem Reviewmentioning
confidence: 99%
“…There are mainly used combinations of MW radiation and convective drying (CD) [1,2], MW radiation and vacuum [1], infrared (IR) radiation and CD [4,5], ultrasound and CD [6], MW, IR radiation and CD [9], discrete IR and CD [5], filter and CD [10][11][12].…”
Section: Problem Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Vibration is a promising way for the intensification of drying [1], especially for porous media. The present work is focused on the study of the effect of vibration to assist moisture migration inside these materials.…”
Section: Introductionmentioning
confidence: 99%